Ukraine’s poor majority: exploring the driving factors of subjective poverty - Homonchuk, O (2020)
Existing scholarship indicates that there are divergences between objective and subjective poverty; yet subjective poverty remains under-researched and not well understood. This research contributes to addressing this gap by identifying and exploring influential factors contributing to high rates of subjective poverty in Ukraine, where nearly 70 per cent of people self-identify as being poor. This rate is surprisingly high given that the World Bank and the National Statistical Service of Ukraine estimate poverty in the country to be around 30 per cent. To understand the drivers of high rates of subjective poverty, the thesis investigates the questions ‘what does self-identification as poor entail in the context of Ukraine?’ and ‘why does the attribution of subjective poverty not correlate with income and material circumstances?’ The questions are explored through a qualitative case study in Rivne city in Western Ukraine, using recognition theory as the main theoretical lens. The analysis draws on data from 50 in-depth semi-structured interviews across low- and high-income groups and across three age groups, with individuals ranging from 20 to 81 years old. Amongst the 50 participants, 39 were subjectively poor, 11 of whom were high-income. The thesis posits that self-identifying as poor is simultaneously a claim of deservingness for a better life, and an internalization of negative stereotypes associated with low social status. In the context of Ukraine, self-identification as poor also has a strong element of collective identity and is accompanied by a binary understanding of inequality, with a perception of a large poor majority and a small rich elite. Consequently, for subjectively poor participants, the average Ukrainian is seen as poor. Moreover, structural explanations of poverty dominate, making it less shameful to self-identify as poor compared to other contexts, in which poverty is associated with individualistic failure.